1999
DOI: 10.1021/jp983553t
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects in the Enantiomeric Electro-Oxidation of d- and l-Glucose on Pt{643}S

Abstract: The temperature dependence of the enantioselective adsorption of d- and l-glucose on a chiral Pt{643}S electrode is reported. The contribution to the electro-oxidation current of the initial adsorption of the glucose molecule on {111} terrace sites is used to determine a difference in the activation energy of adsorption between d- and l-glucose on Pt{643}S. A value of approximately 1.4 kJ mol-1 is obtained. When this value is converted into a diastereomeric product ratio, the mole percentage of the major produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 16 publications
4
118
0
1
Order By: Relevance
“…Electrochemical measurements have also shown that the rates of d-and lglucose electro-oxidation on stepped-kinked Pt surfaces are enantiospecific [12][13][14]. It is the kinks on the step edges that impart chirality to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical measurements have also shown that the rates of d-and lglucose electro-oxidation on stepped-kinked Pt surfaces are enantiospecific [12][13][14]. It is the kinks on the step edges that impart chirality to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…[15] In this study, enantiospecific electrochemical oxidation of glucose was demonstrated on Pt(643) and Pt(-6-4-3) surfaces. Recent studies show that chiral cyclodextrin based coatings applied to a three-transducer microsystem shows distinct chiral discrimination for different compounds.…”
Section: Electrochemical Selectivitymentioning
confidence: 77%
“…They have been produced by decorating the surfaces of achiral substrates by chiral molecules, or by introducing defects in the single crystals which exposes chiral kink sites. [6][7][8][9][10][11][12][13][14][15][16][17] It was shown that chiral surfaces can also be produced by electrodeposition technique. [18,19] Unlike other vacuum techniques, electrodeposition is cheaper and can be carried out at ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic voltammetry has been used to study the electrooxidation kinetics of glucose and other sugars on an array of naturally chiral platinum electrode surfaces in aqueous solutions. [44,[54][55][56] These studies have shown that the rates of D-glucose and L-glucose oxidation on naturally chiral Pt electrodes can differ by as much as a factor of three. As in the case of enantioselective hydrogenation on the chirally templated Pt catalysts, the enantioselectivities of glucose oxidation are influenced by the presence of modifiers adsorbed from solutions.…”
Section: Enantioselectivity Of Naturally Chiral Metal Surfacesmentioning
confidence: 99%